PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN REPRODUKSI TERHADAP TINGKAT PENGETAHUAN REMAJA AWAL SEKOLAH DASAR DI DAERAH WISATA BANDUNGAN, KABUPATEN SEMARANG TAHUN 2016 - Letisa Azelia Astri; Sri Winarni; Yudhy Dharmawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
The problems faced by vulnerable early adolescents include promiscuity, early marriage, abortion and sexual transmitted infections such as HIV/AIDS. In some major cities, around 21-30% of adolescents had sexual intercourse. The number of HIV cases at Semarang Regency were 63 cases, while as many as 19 cases of AIDS. The purpose of this study was to analyze the effect of materials and methods of reproductive health education to knowledge level of early adolescent of elementary school in the tourist area Bandungan, Semarang regency. This study was an experimental study (true experimental) using the design of a randomized block design. These samples included 54 students grade 5. Data were analyzed by univariate and bivariate analysis with two-way anova test. The results show there is a difference between the material knowledge of the reproductive organs and puberty (p=0,0001). There was no difference between treatment groups knowledge of lectures, group discussions and brainstorming (p=0,398). The average post-test score highest reproductive material by using group discussions, namely 81,00 and highest average puberty material using the method of brainstorming is 68,89. There is no mutual interaction between materials and methods of reproductive health education to the level of knowledge (p=0,159).The schools should cooperate with the local health clinic that made the program increased knowledge of reproductive health and reproductive organs material puberty. In giving the material reproductive organs, can be used the method of discussion groups and on the provision of material puberty, it can be used a method of brainstorming.